The assessment of carrying capacity of marine fishery resources in China - Liu, Zhaoyang; Lu, Wenhai; Wang, Tao; Zhang, Yujia; He, Long; Yang, Lu; Deng, Lijing (Frontiers in Marine Science, 2025)
IntroductionThe sustainable development of marine fisheries has been a major concern, with the carrying capacity of marine fishery resources becoming a focal point of research.MethodsThis study, utilizing remote sensing data, marine capture fisheries catch data, and fishing effort data from 2013 to 2020, aims to determine the maximum sustainable yield using a surplus production model and provide a comprehensive assessment of the status and potential of China’s marine fishery resources.ResultsThe results indicate that China’s marine fishery resources exhibit significant regional variability, with the East China Sea contributing the largest share of catch and maintaining sustainability, while regions such as the South China Sea, Yellow Sea, and Bohai Sea have exceeded their ecological carrying capacities. Correlation analysis highlights that nutrient levels and water quality (e.g., chemical oxygen demand) are critical for resource stability, while the distribution and management of protected areas further influence carrying capacity.DiscussionThis study contributes to the development of more effective fishery policies, aiming to balance economic benefits with ecological health. By understanding these dynamics, policymakers can better address the challenges facing sustainable marine fisheries.